Fertility In Oncology Patients (Texas Journal of Medical Science, 2024)
This article reviews the current state of fertility preservation for cancer patients, emphasizing the impact of cancer treatments on reproductive health and recent advancements in preservation techniques. Treatments such as chemotherapy, radiation, and specific surgeries often lead to compromised fertility, creating challenges for patients who wish to conceive post-recovery. The article highlights the effectiveness of various fertility preservation options, including oocyte, sperm, embryo, and ovarian tissue cryopreservation, while addressing their limitations and success rates based on factors like age and treatment type. Additionally, the review explores accessibility issues, ethical considerations, and the importance of patient education. The findings underscore the need for improved awareness and policy support to ensure fertility preservation is available to all cancer patients who may require it.